Group dynamics and team interventions : understanding and improving team performance - Franz, Timothy M. (Malden, MA : Blackwell Pub., 2012)
Strong teams can be one of the greatest strengths of an organization--just as poor teams can spell disaster. Group Dynamics and Team Interventions brings research and practice together to offer proven application and intervention techniques to help optimize team functioning in the workplace. A benefit to academics and practitioners alike, this book provides readers with a better understanding of the dynamics that inform team behavior, along with assessment tools and practical techniques to create and maintain high-performing teams.
Introduction to Teams -- Methods of Assessing and Evaluating Team Functioning -- Team Theories and Concepts -- Understanding Culture and Diversity -- Preparing the Environment for Teamwork -- Improving Small Group Communication and Trust -- Improving Creativity and Innovation -- Improving Problem Solving and Decision Making -- Understanding Cohesion and Collaboration -- Reducing Dysfunctional Conflict and Improving Cooperation -- Influence, Power, and Leadership -- Working in Virtual Teams -- Searching for Synergy: Creating a High-Performing Team -- Appendix: Improving Team Meetings.
Includes bibliographical references and index.
Keywords: Social groups -- Psychological aspects; Teams in the workplace; Diversity in the workplace; Leadership -- Psychological aspects; 0; Multiculturalisme en milieu de travail; Leadership -- Aspect psychologique; Diversity in the workplace; Leadership -- Psychological aspects; Social groups -- Psychological aspects; Teams in the workplace; Psychologie; Teamwork; Gruppe; Grupper -- psykologiska aspekter; Arbetsgrupper